Republic of Equatorial Guinea : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
This report discusses the IMF estimates and projections of the Republic of Equatorial Guinea's central government financial operations, 2001-06; the tax system as of march 2007; public investment program during 2004-06 (execution) and 2007-08 (budgeted); monetary survey during 2001-06; details of central bank and commercial bank assets during 2001-06; fiscal indicators during 2001-06; and estimates on public debts during 2001-06, et cetera.